Are Markets Inclusive for the Poor? - Acosta, Pablo (Archīum Ateneo, 2007)
Building on earlier work by Banerjee and Duflo (2007) [“The Economic Lives of the Poor” in Journal of Economic Perspectives 21(1):141-167], this paper uses survey data from 9 countries in order to shed further light on one aspect of the economic lives of the poor: their access to markets. It develops a framework that could be used to map market inclusiveness, and then applies this to a number of markets that are critical to reducing poverty and achieving the Millennium Development Goals (MDGs). These “market heat maps” help to illustrate the extent of the challenges and in some cases reveals potential opportunities in growing more inclusive markets in water, financial services and labor.